A LITERATURE REVIEW ON USING AI CHATBOT APPLICATION TO ENHANCE STUDENTS PERFORMANCE ON STEAM - Dahlan, Harris R.; Saputra, Rizqiya Windy; Sahid, Hirawan Nur (Jurnal Review Pendidikan dan Pengajaran, 2025)
The rapid development of technology demands continuous innovation of using artificial intelligent in aspect of education, social and economics is very intense and massive. Chatbot as the one kind the artificial intelligence is taking a big part in helping customer getting their needs and reduce the company reduce the worker cost. In applications in the educational sector, chatbot applications are used as intermediaries to improve students' abilities in various aspects such as STEAM (Science, Technology, Engineering, Art and Math) learning materials. However, the existence of chatbots does not always provide convenience or direct impact because non-technical problems can arise from the school, students or education processes. This study offers an overview on chatbots in terms of definition, usage, advantages and their evolution from the theory which triggered these systems to current implementation using the some available libraries in Javascript. Javascript as one of the popular programming languages used today has many libraries such as Botpress, Microsoft Bot Framework, Botkit and others which can be used to design, develop and implement chatbot applications to help the learning process. Finally, This research is trying to provide valuable insights and to find the right chatbot application model to be used in ai chatbot application development and understand the user's condition directly when interacting.